2005
DOI: 10.1177/089686080502500409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraperitoneal Pressure and the Effect of Different Osmotic Agents on Intraperitoneal Pressure in Children

Abstract: Objectives To establish intraperitoneal pressure (IPP) in a relatively large pediatric study group and to study the effects of a 3.86% glucose solution and a 7.5% icodextrin solution on IPP during a 4-hour dwell. Design IPP was measured with the patient in a supine position. The intraperitoneal volume (IPV) was 1200 mL/m2 with a 1.36% glucose solution. The influence of dialysis solutions was obtained by performing two 4-hour peritoneal equilibration tests (PETs) with 3.86% glucose and 7.5% icodextrin as test s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In this context, it is not surprising that in some studies, waist circumference significantly correlated with IPP [10]. This differs in paediatric population, where visceral fat is less relevant and BSA truly reflects the growth of the children, so that for a given IPV, small children with small BSA develop more IPP than those with higher BSA [19].…”
Section: Discussionmentioning
confidence: 98%
“…In this context, it is not surprising that in some studies, waist circumference significantly correlated with IPP [10]. This differs in paediatric population, where visceral fat is less relevant and BSA truly reflects the growth of the children, so that for a given IPV, small children with small BSA develop more IPP than those with higher BSA [19].…”
Section: Discussionmentioning
confidence: 98%
“…Theoretically, increasing DV recruits more peritoneal membrane surface area for better uremic toxin clearance and larger UF volume. Many studies have revealed a negative linear correlation between mean IPP and UF volume [7,9]. Other studies addressed that patients are well tolerated by adult and pediatric PD patients with subjective discomfort judgment when the IPP levels are maintained at less than 18 cm H 2 O and reaching optimal UF volumes [7,10].…”
Section: Traditional Methods Used To Determine the Pd DVmentioning
confidence: 99%
“…Many studies have revealed a negative linear correlation between mean IPP and UF volume [7,9]. Other studies addressed that patients are well tolerated by adult and pediatric PD patients with subjective discomfort judgment when the IPP levels are maintained at less than 18 cm H 2 O and reaching optimal UF volumes [7,10]. Applying IPP measurement as part of adjusting DV can thus be decided along with the subjective tolerance levels of adult patients and the objective observation by a physician in clinical settings.…”
Section: Traditional Methods Used To Determine the Pd DVmentioning
confidence: 99%
“…PD efficiency varies with prescribed fill volume but it is well known that optimal fill volume is a patient's individual parameter [12,13] which should be adapted to the patient's body surface area [1,6]. If the dialysis target is to remove more uremic toxins we should use larger intraperitoneal volumes (IPV) because they increase the peritoneal surface area available for the exchange and enable to achieve greater solutes clearance [7,12,14,15].…”
Section: Importance Of Fill Volumementioning
confidence: 99%